Late Presentation of Cryptococcus gattii Meningitis in a Traveller to Vancouver Island: A Case Report - Ron Levy; Johann Pitout; Patricia Long; M John Gill (Canadian Journal of Infectious Diseases and Medical Microbiology)
Since 1999, Cryptococcus gattii has been identified as a primary pathogen on Vancouver Island in British Columbia, and it has resulted in infection of both people and animals living in that area. A previously healthy 45-year-old female resident of Alberta developed C gattii infection 11 months after travelling to an endemic region of Vancouver Island. A case of an immunocompetent patient, with an atypically long incubation time, who presented with subacute meningitis secondary to disseminated pulmonary cryptococcosis is presented. The present report highlights the need for clinical vigilance in treating patients presenting with atypical pulmonary infections or meningitis who have been holiday travellers to endemic areas of Vancouver Island.